Identifying new buffer areas for conserving waterbirds in the mediterranean basin: the importance of the rice fields in Extremadura, Spain - Sánchez Guzmán, Juan Manuel; Morán López, Ricardo; Masero Osorio, José Antonio; Corbacho Amado, Casimiro; Costillo Borrego, Emilio; Villegas Sánchez, María Auxiliadora; Santiago Quesada, Francisco (Biodiversity and Conservation, 2007)
The impact of wetland loss on migratory waterbirds can be mitigated by the presence of anthropogenic habitats such as rice fields. In the Mediterranean basin, wetlands have been drained and altered to such a degree that their very existence is threatened. It is, therefore, essential to identify key buffer areas in the basin to develop conservation strategies for migratory waterbirds. In Extremadura, continental SW Spain, 30,000 ha of new rice fields have created since the 1960s. The present study describes for the first time the waterbird community associated with these inland rice fields, and addresses the question of the potential value of this area in buffering the loss of natural wetlands for populations of waterbirds using the East Atlantic Flyway (EAF). The waterbird community studied consisted of 45 species, with population levels reaching values of international importance (>1% of the biogeographical population using EAF) for the Common Crane Grus grus (19%), Black-tailed Godwit Limosa limosa (1.2%), Black-winged Stilt Himantopus himantopus (1.2%), and Cattle Egret Bubulcus ibis (1%). The presence of these rice fields may be modifying the wintering and/or feeding sites of some waterbird species such as the Common Crane and Black-tailed Godwit. Unfortunately, there is no legal protection for this area. We propose the designation of these rice fields as a Special Protection Area for birds. peerReviewed